When disaster risk management systems fail: the case of Cyclone Idai in Chimanimani District, Zimbabwe - Munsaka, Edson; Mudavanhu, Chipo; Sakala, Lucy; Manjeru, Pepukai; Matsvange, Diego (SpringerOpen, 2022)
On 14 March 2019, Zimbabwe was hit by Cyclone Idai, leaving immeasurable destruction of unprecedented magnitude in its wake. In Chimanimani District, many lives were lost, many people were reported missing, and others were displaced. The question that immediately comes to mind is: Was the country prepared to manage the Cyclone Idai disaster? Reflecting on the community experiences, the purpose of this research was to interrogate the strength of the disaster risk reduction legislation and institutions in Zimbabwe in the face of meteorological hazards. The research also evaluated the extent of the impact Cyclone Idai had on the Chimanimani communities and the factors that increased the vulnerability to the cyclone. A mixed method approach that involved 1180 participants was used. The study found that disaster risk management legislation and institutions in Zimbabwe are weak. Cyclone Idai resulted in the loss of many human lives, loss of livelihoods, and massive damage to infrastructure. The cyclone exposed capacity and policy gaps in Zimbabwe’s disaster risk management system. The study makes a number of recommendations, including strengthening disaster legislation and policy, and disaster risk governance. Given the communities’ response to the disaster occurrence, the study also recommends strengthening social capital.